Aligning Humanistic Psychology and Islamic Education: A Theoretical Dialogue between Carl Rogers and Abraham Maslow - Dewi, Maylani Rahmawati; Fauzi, Amin (Jurnal al-Thullab, 2025)
Contemporary Islamic education faces the challenge of addressing students’ psychological needs while preserving its moral and theological foundations amid the growing influence of Western humanistic psychology. This study critically examines the theoretical relationship between the humanistic psychology of Carl Rogers and Abraham Maslow and Islamic education through a philosophical dialogue approach. Using qualitative library research, the study analyzes 54 reputable sources published between 2021 and 2025 and indexed in Scopus, Web of Science, and SINTA. The analysis employs thematic reduction and integrative synthesis to identify convergences, tensions, and mechanisms of conceptual reconstruction. The findings indicate that humanistic principles such as empathy, learner-centered learning, and intrinsic motivation possess strong pedagogical relevance but require a transcendental value framework to avoid normative limitations. Through critical reconstruction, self-actualization is reoriented toward the formation of the complete human being, while unconditional positive regard is reframed within the ethical principle of enjoining good and forbidding evil. The study concludes that the Islamic–humanistic framework functions as a pedagogical bridge between psychosocial well-being and spiritual objectives, with broader implications for SDG 4 and SDG 16.